Outcome of children born to human immunodeficiency virus positive mothers - A retrospective study - Malpani, Preeti; Biswas, Manju; Kale, Vishal (Indian Journal of Child Health, 2016)
Background: Mother-to-child transmission of human immunodeficiency virus (HIV) is a major route of new infections in children. The use of anti-retroviral therapy and nevirapine to mother-baby pairs has shown to be quite effective in preventing the transmission of virus from mother-to-child. Objectives: To analyze the incidence of HIV transmission in children born to HIV-infected pregnant women and to analyze the outcome of these children. Methods: This retrospective study was conducted in a tertiary care referral hospital of central India for a period of 3 years. Data analysis of the mothers with HIV-positive serology up to their delivery and follow-up of their babies for 18 months was performed. Perinatal mortality rate (PMR) and neonatal mortality rates (NMRs), mother-to-child transmission rate, and the outcome of their children on the basis of various factors - such as maternal CD4 count, treatment taken, and feeding practices - were analyzed. Results: 161 HIV-positive mothers gave birth to 164 babies (including 1 triplet and 1 twin) during the study period. An incidence of mother-to-child transmission was 8.06% and it was influenced by maternal CD4 count, maternal comorbidities, mode of delivery, and feeding practices. In our study, PMR was 48.78/1000 live births; NMR was 54.87/1000 live births as compared to 25/1000 live births in children born to seronegative mothers. Conclusion: The risk of vertical transmission of HIV from mother-to-baby was 8%. Maternal HIV transmission is the primary means by which infants become infected. Hence, the prevention of maternal HIV transmission is of paramount importance.